Clients’ depth of experiencing and narrative-emotion processes in psychotherapy - Aleixo, A.; Pires, A. P.; Angus, L.; Silva, D. S.; Santos, J. M.; Vaz, A. (Journal of Constructivist Psychology, 2026)
Studies of narrative-emotive processes and clients’ depth of experiencing in psychotherapy have gained prominence over the past decades. While their process rating measures have been shown to be associated with positive treatment outcomes, no studies to date have compared them. To address this gap, the current methodological study sought to test the relationship between them: narrative-emotive processes were measured by the Narrative-Emotion Process Coding System (NEPCS) 2.0 and experiencing processes by the Experiencing scale (EXP scale) in a sample of 40 video-recorded sessions of highly expert therapists selected from seven brief psychotherapy modalities. Multilevel regression analyses were performed to capture the relationship between the problem markers, transition markers, change markers, and the depth of experiencing. As hypothesized, we found that the frequency of the three NEPCS subgroups significantly and positively predicted the seven EXP levels. The qualitative analysis showed substantial variability between therapists in EXP frequencies and a higher frequency of transition markers, followed by the problem and change markers. Both measures captured how change occurs. However, while the EXP focused on emotional awareness, the NEPCS was broader and captured the degree of narrative-emotional integration. The EXP scale could be more sensitive in identifying variability between therapists than the NEPCS scale.